The Relationship Between the Jakun Language to Proto Malay: A Comparative Analysis of Basic Vocabulary: (Hubungan Kekerabatan antara Bahasa Jakun dengan Bahasa Melayu Purba: Satu Analisis Perbandingan Kosa Kata Dasar) (Jurnal Bahasa, 2021)
This study discusses the Jakun language spoken by the native Jakun tribe of Peninsular Malaysia. The objective of this study is to compare the basic vocabulary and determine the relationship between the Jakun language with the Proto Malayic language. This study employs the lexicostatistics theory suggested by Swadesh (1955). Furthermore, this study uses the qualitative descriptive method to interpret the data collected in the field. The Jakun basic vocabulary data was obtained using Swadesh's 200-word list (Swadesh 1955). The study found that the Jakun language and Proto Malayic are in the same language family. This study rejects Carey's (1976) claim that the Jakun language has lost its originality and borrows Malay vocabulary. On the contrary, the study reveals that the Jakun language does not borrow from standard Malay but is a branch of the parent language, Proto Malayic. In conclusion, this study hopes to be a catalyst for more studies on Jakun languages elsewhere, as well as on other Orang Asli languages.Keywords: Jakun tribe, Jakun language, Proto Malayic, lexicostatistics, comparative linguistics